DETERMINAN FENOMENA UNDERPRICING PADA PERUSAHAAN GO PUBLIK DI BURSA EFEK INDONESIA - Giovanni Christianto Purnomo, Peter; Suryaningsih, Rosita (FEB-UP Press, 2023)
The phenomenon of underpricing is interesting because it can encourage the achievement of targets for achieving issuer funds during an IPO and investors can obtain high initial returns. This is what makes during the research period the majority of companies conducting IPOs were underpricing. The objective of this research is to obtain empirical evidence regarding the effect of firm size, net profit margin, underwriter reputation, and the percentage of public offerings towards underpricing. Underpricing is also used as a company strategy when IPO, so by applying the lower share price when IPO, companies can sell all the shares offered and obtain funds that are needed. The data used in this study is secondary data. The objects of this research are non-financial companies that conducted IPOs in the 2017-2020 period. The sample selection used a purposive sampling method. The test method used is multiple regression analysis. The results of this study are underwriter reputation has a significant positive effect towards underpricing, the percentage of public offerings has negative significant effect towards underpricing, while firm size and net profit margin have no effect towards underpricing. Underwriter reputation, the percentage of public offerings, firm size and net profit margin have significant effect towards underpricing simultaneously.